Retaining Wall Design As a Landslide Disaster Mitigation Effort On The Enim River South Sumatra, Indonesia - Putra, M. Sang Gumilar Panca; Anggraini, Nita; Wahyuni, Dwi (Sriwijaya Journal of Environment, 2025)
This research focuses on analyzing the stability of three types of retaining walls cantilever, gravity, and sheet pile to address landslide risks along the Enim River in Tanjung Karangan Village, Muara Enim Regency. The village is prone to landslides due to high riverbanks and unstable soil conditions exacerbated by erosion and settlement encroachment. To mitigate these risks, retaining walls are crucial in maintaining slope stability and preventing further erosion. The study utilized Windows Forms methods to perform numerical simulations and evaluate key factors such as the safety factor, sliding resistance, overturning resistance, bearing capacity, and material strength of the designed walls. The cantilever retaining wall design proved effective, achieving safety factors for overturning (1.80), sliding (1.51), and bearing capacity (1.31), making it suitable for implementation at the study location. However, the gravity retaining wall, despite meeting safety requirements for overturning (1.72) and bearing capacity (1.35), failed in sliding, with a safety factor of 1.49, indicating it is not appropriate for this case due to insufficient sliding resistance. The analysis of the sheet pile retaining wall focused on embedment depth and material quality. A steel sheet pile with a length of 9 meters, an embedment depth of 4.82 meters, and material properties of Fy = 450 MPa and E = 2.1 x 105 MPa was determined to be a feasible solution. The findings conclude that both cantilever and sheet pile retaining walls can effectively mitigate slope instability and riverbank erosion, while the gravity retaining wall is not suitable for the given conditions. These results provide valuable insights for future infrastructure development in landslide-prone areas.